The link of the monetary indicator to future inflation in the Euro Area - a simulation experiment - Stéphanie Stolz; Jan Gottschalk (Kiel Institute of World Economics (IfW), 2001)
We examine the indicator property of the monetary indicator for inflation. Using a P*-model, Svensson shows theoretically in a recent paper that the relationship between these two variables is rather tenuous. The present study employs empirical evidence on the relations in his model to quantify its dynamics for the euro area. Moreover, we extend Svensson's analysis by considering different shocks and monetary regimes. It becomes apparent that the system exhibits complicated dynamics and that for most shocks and policy regimes the monetary indicator is not a leading indicator of dangers to price stability in the medium term.
Keywords: E51; E52; 330; Monetary Targeting; Inflation Targeting; Euro Area; Monetärer Indikator; Inflation; Prognoseverfahren; Preisniveau; Europäische Wirtschafts- und Währungsunion; Simulation; Theorie; EU-Staaten